Board Diversity and Firm Performance: Panel Data Evidence from 12 Selected Commercial Banks in Nigeria - Onyekwere, Sixtus Cyprian; Babangida, Nafisah I. (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2022)
Motivated by the continuous but inconclusive and ambiguous evidence on the relationship between board diversity and financial performance, this study aimed at providing new evidence that will enhance the state of knowledge by establishing if board diversity affects the financial performance of listed Banking institutions in Nigeria. The key dependent variables of interest were Return on Assets (ROA) and Return on Equity (ROE) and the independent variables of interest were board gender diversity and board independence. The study sampled 12 listed banks from the Nigerian stock exchange and relied on secondary data from the Bloomberg database and the annual reports of the banking institutions. Panel data methodology was used to analyse the data for the period under review (2015-2019). The results of the study indicated that board gender diversity has a significant positive impact on both ROA and ROE of the banking institutions. Conversely, the findings of the study indicated that board independence has a significant negative impact on both ROA and ROE of banking institutions. The findings of this study are related to Agency and Resource dependence theories and will contribute to meaningful policy reforms that can improve corporate governance, especially in the banking industry. The results of the study strongly recommend the need to increase the number of female directors on the boards of banking institutions. The study further recommends ways in which the contributions of both female and independent directors can be promoted in other to benefit from their presence on the board.